Effect of niacin on phosphorus, calcium, parathormone and vitamin D levels in hemodialysis patients; a double-blinded randomized clinical trial - Ali Mohamadi Najafabadi; Ali Ahmadi; Saeed Mardani (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Electrolyte abnormalities are one of the most common problems in hemodialysis patients. Objectives: The present study was conducted to investigate the effect of niacin on the levels of sodium, phosphorus, calcium, intact parathormone (iPTH), alkaline phosphatase (ALP) and vitamin D in hemodialysis patients. Patients and Methods: In the present double-blinded randomized clinical trial, hemodialysis patients with phosphorus of more than 4.5 mg/dL were included in the study and were treated with niacin. The dose of niacin was increased from 50 mg to 100 mg/d in two stages on a monthly basis. Tests related to the levels of phosphorus, sodium, vitamin D, and calcium were determined before and after the intervention, and the side effects of the treatment were recorded accordingly. Data were analyzed through SPSS version 16. Results: After the intervention, the serum levels of calcium, vitamin D, and sodium increased significantly (P<0.05), while the serum levels of iPTH and phosphate decreased significantly (P<0.05). However, the serum level of ALP did not change significantly (P>0.05). There was no significant difference in the serum levels of calcium, phosphate, vitamin D, sodium, iPTH, and ALP during the intervention in the both men and women (P>0.05). Side effects were not reported in any of the patients. Conclusion: Niacin can increase vitamin D, sodium and calcium and decreased serum levels of phosphate and iPTH in hemodialysis patients. Therefore, it can be administered as an effective and safe supplement in the hemodialysis patients. Trial Registration: This trial protocol was approved by the Iranian Registry of Clinical Trials (identifier: IRCT20190702044076N2; https://en.irct.ir/trial/66567, ethical code #IR.SKUMS. REC.1400.079).